Constituting the Social Basis of the EU: Reflections from the European Margins - Sekulic, Tatjana (PARTECIPAZIONE E CONFLITTO, 2016)
The article addresses significant aspects of the constitution of the European Union’s social basis from the broader perspective of a European space under construction. The specific point of view regards the process of Europeanization through enlargement to the post-socialist Eastern and South European countries, and conditionality as its main instrument. In the light of the five-year moratorium proposed by the Juncker Commission in 2015, the process is examined particularly from its margins by considering the case of Bosnia and Herzegovina (BiH), i.e. the last country in the ‘Western Balkans’, together with Kosovo, that is not yet a candidate for EU membership. The analysis aims to shed light on two different and conflictual forms of agency: first, the institution building process through accession procedures; second, social dissent patterns and citizens’ mobilization in Bosnia and Herzegovina. The purpose is to analyze if and how these diverse agencies cross borders and soften boundaries to constitute an emerging European society. A constant methodological concern of this study is if and how an ethnography of the process may contribute to the analysis of European integration in its complex, non-linear and often contradictory nature (Kauppi 2013)